Thresholds of Change in Children's Literature: The Symbol of the Mirror - Sergio Arlandis; Agustin Reyes-Torres (Springer, 2018)
This article approaches the study of children's literature as a threshold of change that allows readers to explore the reality around them, imagine other worlds and understand other perspectives. Based on the notion of the child's cognitive development organized into four stages -pre-reading, fantastic stage, fantastic-realistic stage and aesthetics stage- reading becomes a resource to combine fantasy and experience where the mirror is a highly suggestive element and prone to hundreds of interpretations and applications as can be seen in the plots of well-known books such as the brother Grimm's Snow White, Lewis Carroll's Through the Looking-Glass, Michael Ende's The Neverending story and J.K. Rowling's The Philosopher's Stone, among others. As a result, as young readers go from one stage to another, the mirror gains greater symbolic complexity and they face the discovery of the self and the other as well as the confrontation between the so-called primary and secondary worlds, reality and the marvelous.